Response of rice residue, tillage and nitrogen management on wheat in rice-wheat cropping system in the Indo-Gangetic Plains of India - Kumar, Arvind; Jat, M.L.; Kumar, Kumar; Tomar, Jaibir; Kumar, Sudhir; Kushwaha, S.R.; Singh, C.B. (Annals of Agricultural Research, 2016)
Rice-wheat (RW) cropping system of the Indo-Gangetic Plains has played a significant role in the food security of India. Field experiments on sandy loam soils was conducted during rabi 2005-06 and 2006-07 at the Research Farm of the Janta Vedic (P.G.) College, Baraut, District-Baghpat (U.P.) to evaluate the impact of different rice residue and tillage practices in main-plots and four nitrogen levels (0, 50 kg, 100 kg and 150 kg N/ha) in sub-plots on crop growth rate, relative growth rate, physiological efficiency and N uptake of wheat (Triticum aestivum L.) grown after rice (Oryza sativa L.). Zero tillage sown treatment resulted in highest CGR and RGR as compared to conventional tillage at all the residue management practices. Both CGR and RGR enhanced with the each successive increase is nitrogen level from 0 to 150 kg/ha, being the highest value at 150 kg N/ha. Physiological efficiency was positively higher in residue retained with zero tillage than residue removed under zero tillage. Residue retained with zero tillage recorded significantly higher uptake of nitrogen by wheat plants as compared to residue incorporated with conventional tillage. The physiological efficiency was higher with 50 kg N/ha. Maximum uptake of nitrogen was observed in 150 kg N/ha which was significantly higher than 100 and 50 kg N/ha. In this study authors have discussed current concerns and possible options for efficient management of rice residue, tillage and nitrogen in the RW cropping system.